The association of interleukin-1 gene polymorphism with chronic rhinosinusitis with and without nasal polyp - Mohamad, Sakinah (2018)
Background: Chronic rhinosinusitis (CRS) is one of the most common and complex chronic inflammatory disease of sinonasal mucosa. Eventhough the pathogenesis of CRS is multifactorial and still unclear, the role of cytokines especially interleukin-1 (IL-1) is being investigated worldwide in different population because of varying results obtained. Objective: To study the association of IL-1 (A and B) gene polymorphisms with chronic rhinosinusitis with nasal polyp (CRSwNP) and without NP (CRSsNP), and other factors related. Methods: This is a case controlled study which include a total of 138 subjects recruited from Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) clinic in Hospital Universiti Sains Malaysia (HUSM). Genotyping of the IL-1A (+4845G, +4845T) and IL-1B (-511C, -511T) was performed with restriction fragment length polymorphism (RFLP) analysis. Results: From 138 participants, there were 61 males (44.2%) and 77 (55.8%) females. The mean [SD] age at diagnosis was 46.6 [13.70] and 34.41 [12.37] years for CRSwNP and CRSsNP, respectively. Majority of the subjects was Malay in origin. Cigarette smoking was significantly associated with CRSwNP and CRSsNP patients (p-value < 0.001). There was a statistical significant association between IL-1B (-511C, -511T) gene polymorphism with CRSwNP and CRSsNP (p-value < 0.001). The CT genotype of IL-1B was markedly increased in CRSwNP subjects. However, there was no significant association found between IL-1A (+4845G, +4845T) and CRSwNP and CRSsNP (p-value = 0.093). No association was found in factors related to CRS, which included asthma, atopy, allergy, aspirin sensitivity and family history of nasal polyp (NP) (p-value of 0.382, 0.382, 0.144, >0.95 and 0.254, respectively). Conclusion: This study indicates an association of IL-1B (-511C, -511T) polymorphism with CRSwNP and CRSsNP in our population, hence there is a possibility of IL-1B involvement in modulating pathogenesis of CRS. There was no significant association of IL-1A (+4845G, +4845T) polymorphism with CRSwNP and CRSsNP, and other factors related.